A study of politics in the Cape Colony from January 1908 to May 1910 - Ross, Barry Kennedy (Department of Historical Studies, 2015)
The period with which this thesis is concerned is one of vital importance in the history of the old Cape Colony and also of very real significance in the past and future development of the Union of South Africa. It was during this period that the Cape Colony made the tremendous decision to unite with the other South African colonies, and the results of that decision are still with us today, and some, indeed, have not been fully worked out even yet. It was the bad fortune of the Cape Colony to enter Union at a time when she was slowly recovering from the effects of a severe depression. At the time of Union, the Colony had barely become solvent and this financial weakness had placed her in an extremely invidious position during the National Convention. Then too at the meetings of that body she lacked the services of two of her most able politicians, J.H. Hofmeyr and W.P. Schreiner. There are a fair number of secondary works which handle this period. The biographies of the two men mentioned above are examples. But no secondary work has dealt with the period as a subject in itself. It has always been related to a personality, and most of the secondary works are clouded by continual references of a personal nature, which make it extremely difficult for form a clear-cut impartial picture of the period. It is hoped that this thesis may in some small way supply that need. As this thesis is concerned purely with politics in the Cape Colony, no attempt has been made to give a comprehensive description of Merriman's administration or of the work of individual Government departments. For this reason press reports, private papers and biographies have been used, rather than official documents. The latter have, of course, been used to provide statistical information where such proved necessary.